Dampak Media Digital terhadap Kemampuan Berbahasa Indonesia Anak Usia Dini - Sitanggang, Agnesia; Mairianta, Beatriz; Syarefi, Fakhira Azzahra; G, Gustiana; Febriana, Ika; Rambe, Luthfiah Amri; Duha, Yulenta Carolin Sitiani (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of digital technology has a significant impact on Indonesian language skills in early childhood. Digital media, such as educational applications and interactive videos, can improve children's language skills by enriching vocabulary and improving communication skills. However, uncontrolled use of digital media can have negative impacts, such as delays in the development of children's vocabulary and verbal skills, due to reduced direct interaction with parents and the environment. Therefore, it is important for parents and educators to use digital media wisely and pay attention to the duration of use and the type of content that is appropriate to support children's language development optimally. This study aims to provide insight into the positive and negative effects of digital media on early childhood language skills and strategies for optimizing its use.